From molecular endpoints to modeling longer-term effects in fish embryos exposed to the elutriate from Doce River - Yamamoto, Flávia Yoshie [UNESP]; Souza, Angie Thaisa Costa; Paula, Vinicius de Carvalho Soares de; Beverari, Isabella [UNESP]; Garcia, Juan Ramon Esquivel; Padial, André Andian; Abessa, Denis Moledo de Souza [UNESP] (Elsevier, 2022)
Sediments represent a major sink and also a main source of contaminants to aquatic environments. An environmental disaster from a mining dam breakage in 2015 in South-East Brazil re-suspended complex mixtures of chemicals deposited in the sediment, spreading contaminants along the Doce River Basin (DRB) major river course. While high levels of contaminants in sediment were well described, toxicological effects in aquatic organisms were poorly investigated. Thus, the effects of these potentially toxic chemicals were assessed in the present study through different endpoints (biochemical to populational levels) in fish embryos of the South-American silver catfish exposed to elutriates from different sites of the DRB. Despite no significant mortality observed, our results showed that exposure to the elutriates, especially those from the closest site to the dam collapse, caused higher deformities rates and DNA damage in the fish embryos than in the control group. Multivariate analysis showed that these sublethal effects may be related to the high levels of metals introduced by mining activities, compromising long-term survival and reproduction success. In addition, it was possible to observe the influence of other sources of pollutants along the river. According to our data, the mathematical model simulated a significant impact on the population density at longer-term exposure, for the sites that showed the most prominent toxicity responses. The fish embryo toxicity test proved to be an effective assay to assess the ecotoxicological effects of the pollutants from a major river contaminated by a mining dam collapse and showed that the survival rate per se was not a suitable endpoint to assess the toxicity of the pollutants. As a consequence, we contributed to shed a light on a potential underestimated impact of pollutants in sediments of the DRB on the native organisms at distinct biological levels of organizations.
Keywords: Biomarkers; Mining activities; Modeling; Sediments; Sublethal effects; Toxicity test